The socioeconomic inequality of households and the process of pedagogical continuity in times of confinement. Argentine Northwest. year 2020 : Noroeste Argentino. Año 2020 (Itinerarios Educativos, 2024)
The purpose of this communication is to analyze the relationship between socioeconomic inequality and the pedagogical continuity process through a descriptive–comparative study that has two databases as a source of information: 1) the National Evaluation of the Pedagogical Continuity Process, surveyed in July 2020, by the Ministry of Education of the Nation, through the Secretariat of Educational Evaluation and Information; and 2) the Household Survey, carried out between June 18 and July 3, 2020, by the National Ministry of Education in conjunction with the UNICEF Argentina Education Program. For data processing, the Statistical Package for the Social Sciences (SPSS) program was used, with which filters were applied to select the geographical area that interests the investigation, frequencies and crossings of the data that will be analyzed. The results reveal that the schools of the NOA register high levels of pedagogical continuity. However, the availability of technological resources mainly affected households with high socioeconomic vulnerability.
Keywords: confinement; NOA; inequality; pedagogical continuity